Situating complexity: information behaviour in the contact zone - Hye Lim Joy Nam (Information Research: An International Electronic Journal)
Introduction.  This short paper addresses the problematic un-situated nature of the holistic framework proposed by Polkinghorne and Given. In 2021, Polkinghorne and Given called for a substantive shift in the information field to a holistic research paradigm. However, framing studies in a contextualised, complex manner has remained an enduring challenge, particularly regarding where information experiences occur.